The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1080/01411920701434094
|View full text |Cite
|
Sign up to set email alerts
|

Can educational experiments both test a theory and inform practice?

Abstract: This article feeds into debate about the feasibility and usefulness of educational experiments by discussing methodological issues arising out of a study which sought causal links between teaching and learning of one aspect of French as a foreign language. The study involved two small-scale experiments which tested a hypothesis regarding the learning of second language grammar within a particular theoretical, and its related pedagogical, framework (Input Processing and Processing Instruction respectively), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
(85 reference statements)
0
12
0
1
Order By: Relevance
“…Further, both Bonetti et al. (2010) in behavioural research andMarsden (2007) in education research have adopted the approach of developing intermediary studies -taking an experimental approach into a practice 2 context - in order to directly address this gap. Bolton and Ockenfels (2008) describe this as losing control in a controlled way.…”
Section: A Comparison Of Designer Activity Using Core Design Situatiomentioning
confidence: 99%
“…Further, both Bonetti et al. (2010) in behavioural research andMarsden (2007) in education research have adopted the approach of developing intermediary studies -taking an experimental approach into a practice 2 context - in order to directly address this gap. Bolton and Ockenfels (2008) describe this as losing control in a controlled way.…”
Section: A Comparison Of Designer Activity Using Core Design Situatiomentioning
confidence: 99%
“…Finally, I raise an issue that is relevant to much experimental educational research: a comparison treatment is usually evaluated in terms of the potential benefits of the experimental treatment, and yet the comparison treatment may have benefits of its own. The outcome measurements in Wong's study tested for morphosyntax, yet the comparison treatment (input with other kinds of comprehension questions), may have had other kinds of benefits such as vocabulary acquisition (as learners can just focus on lexical items to answer the questions), or reading fluency (see Marsden 2007). This is an empirical question, applicable to most educational experiments that evaluate one type of intervention over another.…”
Section: Operationalising Discoursementioning
confidence: 99%
“…"In addition to achievement test scores, attitudinal data were collected from the teachers and pupils, using questionnaires, interviews and focus groups. Attitudinal data suggested that learners found both PI and EI activities new and enjoyable" (Marsden, 2007). The achievement test results among the learners who were in a very early stage of developing a particular grammar concept and who experienced input PI activities (those PI activities forced them to interpret the grammar concept) resulted in statistically significant larger learning gains than EI in all four measures used, namely, listening, reading, writing and speaking.…”
Section: ) Electronic Pen Pal Communication With Individuals From Himentioning
confidence: 93%
“…The achievement test results among the learners who were in a very early stage of developing a particular grammar concept and who experienced input PI activities (those PI activities forced them to interpret the grammar concept) resulted in statistically significant larger learning gains than EI in all four measures used, namely, listening, reading, writing and speaking. For more advance students the advantages of PI instruction were the case too, but less pronounced (Marsden, 2007).…”
Section: ) Electronic Pen Pal Communication With Individuals From Himentioning
confidence: 99%